Icefall [videorecording (DVD)] - Mahaffey, George (Screenwriter); Isles, Steve; Kinnaman, Joel, 1979-; Myers, Cara Jade; Sensmeier, Martin, 1985-; Nixon, De'Vaughn; Gustavsson, Frida, 1993-; Trevena, Oliver; Fletcher, Will; Huston, Danny, 1962-; Greene, Graham, 1952-2025 (Decal Releasing, 2026)
An Indigenous game warden arrests a poacher who knows where a crashed plane full of cash is hidden. Hunted by criminals and corrupt cops, the two must team up to escape across a thawing lake.